2014
DOI: 10.1111/jocs.12483
|View full text |Cite
|
Sign up to set email alerts
|

Tricuspid Valve Surgery in Patients With Idiopathic Hypereosinophilic Syndrome

Abstract: A 53-year-old female with idiopathic hypereosinophilic syndrome underwent recurrent tricuspid valve replacement for Löffler's endocarditis. We review the literature on tricuspid valve surgery in patients with this uncommon disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
(58 reference statements)
0
1
0
Order By: Relevance
“…Selvi et al reported a case where montelukast and ketotifen provided significant relief from HES-related arthritis and rash 12. In rare instances, splenic or cardiac surgery may also be performed to improve organ function after proper evaluation 37. In this review, the treatment of skin lesions was mainly focused on oral or topical steroids and PUVA therapy in addition to other immunosuppressive agents.…”
Section: Discussionmentioning
confidence: 99%
“…Selvi et al reported a case where montelukast and ketotifen provided significant relief from HES-related arthritis and rash 12. In rare instances, splenic or cardiac surgery may also be performed to improve organ function after proper evaluation 37. In this review, the treatment of skin lesions was mainly focused on oral or topical steroids and PUVA therapy in addition to other immunosuppressive agents.…”
Section: Discussionmentioning
confidence: 99%